Study on Verifying the Effectiveness of Non-face-to-face Youth Volunteering in Improving Self-Esteem among Children of Deaf Adults (CODAs) - Won, Doyeon; Yang, Eunice; Yi, Seojin; Cho, Jeongwoo; Kim, Alex; Lee, Seoeun; Choi, Joonhee (Technium Social Sciences Journal, 2021)
The goal of this study is to evaluate the effectiveness of youth volunteering in increasing the self-esteem of hearing children of deaf adults (CODAs), who commonly start taking care of their parents from a young age. To this end, an experimental study based on the non-equal comparison groups design was applied to a experimental group of 4 participants and a control group of 3 participants, selected based on the recommendation from expert social workers from the M General Social Welfare Center in P City. The volunteer programs, conducted non-face-to-face due to COVID-19, were centered on art activities such as drawing one's own dreams, decorating flowers, and customizing pencil cases. Repeated measures analysis of variance (rANOVA) was conducted to verify the effectiveness of volunteering, and the analysis results are as follows. First, in both the experimental group and the control group, CODAs’ self esteem increased after the program was carried out. Second, while the growth effect appeared in both groups, the slope of increase in the self-esteem of the experimental group was significantly higher than that of the control group. Accordingly, the effectiveness of volunteering to improve CODAs' self-esteem was verified. This study suggests academic and practical implications based on these findings.